FROM THE AVANT-GARDE TO THE DIGITAL AGE: HOW TECHNOLOGY CHANGED THE ART OF MUSIC IN THE TWENTIETH CENTURY - LIAKHOVYCH, Artem; KOCHERZHENKO, Oleksandr; KOPOT, Volodymyr; TYSHCHENKO, Mykhailo; ISHCHENKO, Katerina (Studia Universitatis Babes-Bolyai Musica, 2025)
The twentieth century is characterized by the rapid development of technology, including in the field of sound recording and the production of electric musical instruments. The purpose of this study is to find out what changes technological innovations have led to in the art of music, and what areas of musical art they have led to. The paper presents tables of key inventions in the field of sound recording, development of electric musical instruments and software that were key to the development and emergence of new areas of musical art. The role of electric musical instruments is considered from the standpoint of enriching the timbral palette of musical art: electronic technologies open up the possibility of generating timbres that have no analogues among acoustic instruments and thus significantly enrich the field for creative research. The role of technology in the formation of rock music, electronic dance music, algorithmic music, and the emergence of folk electronics is clarified. The author shows the sociological aspect of musical creativity, which in the XX century is characterized by the acceleration of information exchange between musicians, the expansion of the amount of musical material available for listening to users due to the possibility of their fixation on material media, and at the end of the XX century – transmission via the Internet.